(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article presents a review of the literature on the problem of therapy of metabolic polyneuropathy in patients with diabetes mellitus type 2 (DM2) and chronic alcohol intoxication. The most common variant of diabetic neuropathy (30-50% of patients with DM) is diabetic polyneuropathy (DPN), manifested by severe pain syndrome. The development of symmetrical distal sensory polyneuropathy (SDSP) in patients with DM2, which is characterized by intense pain neuropathic syndrome, occurs in 20-30%, and the frequency of its representation increases as the disease progresses. Vitamins B1, B6, B12 have a neurotropic effect, the deficiency of each of which leads to the formation of polyneuropathy. The appointment of a combination of thiamine, pyridoxine, cyanocobalamin well relieves pain and eliminates sensitivity disorders.